PENGARUH Saccharomyces cerevisiae TERHADAP KADAR LOVASTATIN DALAM ANGKAK YANG DIHASILKAN DARI FERMENTASI BERAS OLEH Monascus purpureus JMBA - Evi Triana; Novik Nurhidayat (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2009)
Fermented rice by Monascus purpureus, namely angkak, produces lovastatin. Lovastatin has been believed and studied as antihypercholesterolemic agent. The level of lovastatin in natural occurred product is very low, result in high price in the market. Something which could increase lovastatin amount is required to be investigated. Therefore a study about the effect of Saccharomyces cerevisiae in stimulating the growth of M. purpureus and the best time for adding S. cerevisiae in order to yield optimal amount of lovastatin has been conducted. The result showed that the best time for addition S. cerevisiae yieldied optimal amount of lovastatin is the day 12.